Protecting Traders at the Fish Market in Medan City in Relation to Subscription-Based Parking: An Analysis from the Perspective of Maslahah Mursalah - Perangin Angin, Rachmat Azra’I; Permata , Cahaya (Law and Economics, 2025)
Trader protection in this context is a highly significant issue. Small-scale traders often lack the capacity to quickly adapt to new policies that directly impact their economic activities. This study aims to understand the regulations surrounding subscription-based parking, to examine its impact in Medan City, and to elaborate on the concept of trader protection in response to the subscription-based parking policy from the perspective of Maslahah Mursalah. The research employs an empirical juridical method using a Living Case Study Approach and a Conceptual Approach. Data collected in the field is supported by interviews and document studies, and analyzed qualitatively. The findings indicate that the implementation of the subscription-based parking system has caused both conflict and satisfaction among traders and consumers within the designated parking zones. From the perspective of Maslahah Mursalah, trader protection by the government should include public awareness campaigns about the benefits and workings of the subscription-based parking system. Furthermore, the government is expected to conduct regular evaluations of the implemented system to ensure that the policy operates as intended and can be improved when necessary